Thermoelectric conversion material layer and method for producing same
Patent Information
- Application Number
- JP2021511900
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-03-26
AI Technical Summary
【0007】 本発明によれば、熱電半導体組成物の塗布膜からなる熱電変換材料層中の熱電変換材料の電気伝導率が向上された、熱電性能の高い熱電変換材料層及びその製造方法を提供することができる。
Smart Images

Figure 0007631188000002 
Figure 0007631188000003 
Figure 0007631188000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoelectric conversion material layer and a method for producing the same. [Background technology]
[0002] 2. Description of the Related Art Conventionally, as one of the means for effectively utilizing energy, there has been a device that directly converts thermal energy into electrical energy and vice versa using a thermoelectric conversion module having a thermoelectric effect such as the Seebeck effect or the Peltier effect. As the thermoelectric conversion module, the use of so-called π-type thermoelectric conversion elements is known. The π-type is configured by providing a pair of electrodes spaced apart from each other on a substrate, for example, providing a P-type thermoelectric element on one electrode and an N-type thermoelectric element on the other electrode, also spaced apart from each other, and connecting the upper surfaces of both thermoelectric materials to the electrodes of the opposing substrate. Also, the use of so-called in-plane type thermoelectric conversion elements is known. The in-plane type is configured by alternately providing P-type thermoelectric elements and N-type thermoelectric elements in the in-plane direction of the substrate, for example, by connecting the lower parts of the junctions between the two thermoelectric elements in series with an electrode interposed therebetween. In this situation, there is a demand for improved flexibility, thinning, and improved thermoelectric performance of thermoelectric conversion modules. To satisfy these demands, for example, resin substrates such as polyimide are used as substrates for thermoelectric conversion modules from the viewpoint of heat resistance and flexibility. In addition, bismuth telluride-based materials are used as N-type thermoelectric semiconductor materials and P-type thermoelectric semiconductor materials from the viewpoint of thermoelectric performance, and for example, a thermoelectric semiconductor composition containing a resin and a thermoelectric semiconductor material is formed in the form of a coating film by screen printing or the like from the viewpoint of flexibility and thinning (Patent Document 1, etc.). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2016 / 104615 Summary of the Invention [Problem to be solved by the invention]
[0004] However, since the thermoelectric semiconductor material used in the thermoelectric conversion module is formed as a thermoelectric conversion material layer in the form of a coating film from a thermoelectric semiconductor composition containing a resin, a thermoelectric semiconductor material, etc., the obtained thermoelectric conversion material layer could not obtain a sufficiently high electrical conductivity and had insufficient thermoelectric performance.
[0005] In view of the above, an object of the present invention is to provide a thermoelectric conversion material layer having high thermoelectric performance, in which the electrical conductivity of the thermoelectric conversion material in the thermoelectric conversion material layer made of a coating film of a thermoelectric semiconductor composition is improved, and a method for producing the same. [Means for solving the problem]
[0006] As a result of intensive research by the inventors to solve the above problems, they discovered that a coating film of a thermoelectric semiconductor composition contains many voids, and that by reducing the volume of these voids, a thermoelectric conversion material layer having a high filling rate of thermoelectric conversion material can be obtained, thereby providing high electrical conductivity, and thus completed the present invention. That is, the present invention provides the following (1) to (10). (1) A thermoelectric conversion material layer comprising a coating film of a thermoelectric semiconductor composition, the thermoelectric conversion material layer having voids, and a filling rate defined as a ratio of an area of the thermoelectric semiconductor composition to an area of a longitudinal cross section including a center of the thermoelectric conversion material layer, the filling rate being equal to or greater than 0.800 and less than 1.000. (2) The thermoelectric conversion material layer according to (1) above, wherein the thermoelectric semiconductor composition contains a thermoelectric semiconductor material, and the thermoelectric semiconductor material is a bismuth-tellurium-based thermoelectric semiconductor material, a telluride-based thermoelectric semiconductor material, an antimony-tellurium-based thermoelectric semiconductor material, or a bismuth selenide-based thermoelectric semiconductor material. (3) The thermoelectric conversion material layer according to (1) or (2) above, wherein the thermoelectric semiconductor composition further contains a heat-resistant resin. (4) The thermoelectric conversion material layer according to any one of the above (1) to (3), wherein the heat-resistant resin is a polyimide resin, a polyamide resin, a polyamideimide resin, or an epoxy resin. (5) The thermoelectric conversion material layer according to any one of (1) to (4) above, wherein the thermoelectric semiconductor composition further contains an ionic liquid and / or an inorganic ionic compound. (6) The thermoelectric conversion material layer according to any one of (1) to (5) above, wherein the thermoelectric conversion material layer has a thickness of 1 to 1000 μm. (7) The thermoelectric conversion material layer according to any one of (1) to (6) above, wherein the packing ratio is 0.850 to 0.999. (8) A method for producing a thermoelectric conversion material layer consisting of a coating film of a thermoelectric semiconductor composition, comprising: (A) a step of forming a thermoelectric conversion material layer; (B) a step of drying the thermoelectric conversion material layer obtained in the step (A); (C) a step of pressurizing the thermoelectric conversion material layer after drying obtained in the step (B); and (D) a step of annealing the pressurized thermoelectric conversion material layer obtained in the step (C). (9) The method for producing a thermoelectric conversion material layer according to (8) above, wherein the annealing is carried out at a temperature of 250 to 600°C. (10) The method for producing a thermoelectric conversion material layer according to (8) or (9) above, wherein the pressure is applied at 1.0 to 60 MPa. Effect of the Invention
[0007] According to the present invention, it is possible to provide a thermoelectric conversion material layer having excellent thermoelectric performance, in which the electrical conductivity of the thermoelectric conversion material in the thermoelectric conversion material layer made of a coating film of a thermoelectric semiconductor composition is improved, and a method for producing the same. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a diagram for explaining the definition of a vertical cross section of a thermoelectric conversion material layer according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view illustrating a vertical section of a thermoelectric conversion element layer obtained in an example or a comparative example of the present invention. [Diagram 3]1A to 1C are explanatory diagrams showing an example of a method for producing a thermoelectric conversion material layer according to the present invention in the order of steps. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Thermoelectric conversion material layer] The thermoelectric conversion material layer of the present invention is a thermoelectric conversion material layer consisting of a coating film of a thermoelectric semiconductor composition, and is characterized in that the thermoelectric conversion material layer has voids, and when the filling rate is defined as the ratio of the area of the thermoelectric semiconductor composition to the area of a vertical cross section including a central portion of the thermoelectric conversion material layer, the filling rate is equal to or greater than 0.800 and less than 1.000.
[0010] <Vertical cross section of thermoelectric conversion material layer> The definition of "a vertical cross section including the central portion of a thermoelectric conversion material layer" in this specification will be explained with reference to the drawings. FIG. 1 is a diagram for explaining the definition of the longitudinal section of a thermoelectric conversion material layer of the present invention, in which (a) is a plan view of a thermoelectric conversion material layer 2, which has a length X in the width direction and a length Y in the depth direction, and (b) is a longitudinal section of the thermoelectric conversion material layer 2, including a void portion 3, formed on a substrate 1a, which longitudinal section includes a central portion C of (a) and has a length X and a thickness D obtained when cut between A-A' in the width direction (shown as a rectangle in the diagram).
[0011] The longitudinal section of the thermoelectric conversion material layer of the present invention will be described with reference to the drawings. 2 is a schematic cross-sectional view for explaining the longitudinal section of the thermoelectric conversion material layer of the embodiment or comparative example of the present invention, (a) is a longitudinal section of the thermoelectric conversion material layer 2s formed on the alumina substrate 1b obtained in Comparative Example 1, the thermoelectric conversion material layer 2s has a longitudinal section consisting of a curve with a length X in the width direction and a value of Dmin and Dmax in the thickness direction, the upper part of the longitudinal section has a concave part and a convex part, and a void part 3b exists in the longitudinal section. (b) is a longitudinal section of the thermoelectric conversion material layer 2t formed on the alumina substrate 1b obtained in Example 1, the longitudinal section of the thermoelectric conversion material layer 2t has a length X in the width direction and a thickness D in the thickness direction [when the values of Dmin and Dmax in (a) of FIG. 2 are slightly different], the upper part of the longitudinal section is approximately linear, and the longitudinal section has a void part 4b with a suppressed number and volume of voids. Dmin means the minimum value of the thickness in the thickness direction of the longitudinal section, and Dmax means the maximum value of the thickness in the thickness direction of the longitudinal section.
[0012] In the thermoelectric conversion material layer of the present invention, the filling rate of the thermoelectric semiconductor composition in the thermoelectric conversion material layer, which is defined as the ratio of the area of the thermoelectric semiconductor composition to the area of a longitudinal cross section including the center of the thermoelectric conversion material layer, is 0.800 or more and less than 1.000, and there are few voids in the thermoelectric conversion material layer. If the filling rate of the thermoelectric semiconductor composition in the thermoelectric conversion material layer is less than 0.800, the number of voids in the thermoelectric conversion material layer increases, making it difficult to obtain excellent electrical conductivity and high thermoelectric performance. The filling rate is preferably 0.810 to 0.999, more preferably 0.850 to 0.999, even more preferably 0.900 to 0.999, and particularly preferably 0.950 to 0.999. If the filling rate is within this range, excellent electrical conductivity is obtained, resulting in a thermoelectric conversion material layer with high thermoelectric performance.
[0013] The thermoelectric conversion material layer of the present invention (hereinafter sometimes referred to as "thin film made of thermoelectric conversion material layer") is made of a coating film of a thermoelectric semiconductor composition. The thermoelectric semiconductor composition preferably contains a thermoelectric semiconductor material and a heat-resistant resin from the viewpoint of shape stability of the thermoelectric conversion material layer, and more preferably contains a thermoelectric semiconductor composition containing a thermoelectric semiconductor material, a heat-resistant resin, and an ionic liquid and / or an inorganic ionic compound from the viewpoint of thermoelectric performance. From the viewpoint of thermoelectric performance, the thermoelectric semiconductor material is preferably used as thermoelectric semiconductor particles (hereinafter, the thermoelectric semiconductor material may be referred to as "thermoelectric semiconductor particles").
[0014] The thickness of the thermoelectric conversion material layer is not particularly limited, but from the viewpoints of flexibility, thermoelectric performance and film strength, it is preferably 1 nm to 1000 μm, more preferably 3 to 600 μm, and further preferably 5 to 400 μm.
[0015] (Thermoelectric semiconductor materials) The thermoelectric semiconductor material used in the present invention is not particularly limited as long as it is a material that can generate a thermoelectromotive force by applying a temperature difference. For example, bismuth-tellurium-based thermoelectric semiconductor materials such as P-type bismuth telluride and N-type bismuth telluride; telluride-based thermoelectric semiconductor materials such as GeTe and PbTe; antimony-tellurium-based thermoelectric semiconductor materials; ZnSb, Zn3Sb 2、 Zinc-antimony thermoelectric semiconductor materials such as Zn4Sb3; silicon-germanium thermoelectric semiconductor materials such as SiGe; bismuth selenide thermoelectric semiconductor materials such as Bi2Se3; β-FeSi2, CrSi2, MnSi 1.73 Examples of thermoelectric semiconductor materials that can be used include silicide-based thermoelectric semiconductor materials such as Mg2Si; oxide-based thermoelectric semiconductor materials; Heusler materials such as FeVAl, FeVAlSi, and FeVTiAl; and sulfide-based thermoelectric semiconductor materials such as TiS2. Among these, bismuth-tellurium based thermoelectric semiconductor materials, telluride based thermoelectric semiconductor materials, antimony-tellurium based thermoelectric semiconductor materials, and bismuth selenide based thermoelectric semiconductor materials are preferred.
[0016] Furthermore, from the perspective of thermoelectric performance, it is more preferable that it is a bismuth-tellurium-based thermoelectric semiconductor material such as p-type bismuth telluride or n-type bismuth telluride. The p-type bismuth telluride has holes as carriers and a positive Seebeck coefficient. For example, Bi X Te3Sb 2-X represented by is preferably used. In this case, X is preferably 0 < X ≤ 0.8, more preferably 0.4 ≤ X ≤ 0.6. When X is greater than 0 and less than or equal to 0.8, the Seebeck coefficient and electrical conductivity increase, and the characteristics as a p-type thermoelectric element are maintained, which is preferable. In addition, the n-type bismuth telluride has electrons as carriers and a negative Seebeck coefficient. For example, Bi2Te 3-Y Se Y represented by is preferably used. In this case, Y is preferably 0 ≤ Y ≤ 3 (when Y = 0: Bi2Te3), more preferably 0 < Y ≤ 2.7. When Y is 0 or more and 3 or less, the Seebeck coefficient and electrical conductivity increase, and the characteristics as an n-type thermoelectric element are maintained, which is preferable.
[0017] The thermoelectric semiconductor particles used in the thermoelectric semiconductor composition are those obtained by pulverizing the above-described thermoelectric semiconductor material to a predetermined size using a pulverizing device or the like.
[0018] The blending amount of the thermoelectric semiconductor particles in the thermoelectric semiconductor composition is preferably 30 to 99% by mass. More preferably, it is 50 to 96% by mass, and still more preferably, it is 70 to 95% by mass. When the blending amount of the thermoelectric semiconductor particles is within the above range, the Seebeck coefficient (absolute value of the Peltier coefficient) is large, the decrease in electrical conductivity is suppressed, and only the thermal conductivity decreases, so that high thermoelectric performance is exhibited, and a film having sufficient film strength and flexibility can be obtained, which is preferable.
[0019] The average particle size of the thermoelectric semiconductor particles is preferably 10 nm to 200 μm, more preferably 10 nm to 30 μm, further preferably 50 nm to 10 μm, and particularly preferably 1 to 6 μm. Within the above range, uniform dispersion is facilitated, and electrical conductivity can be increased. The method of pulverizing the thermoelectric semiconductor material to obtain thermoelectric semiconductor particles is not particularly limited, and the material may be pulverized to a predetermined size using a known fine pulverizing device such as a jet mill, ball mill, bead mill, colloid mill, or roller mill. The average particle size of the thermoelectric semiconductor particles was obtained by measurement using a laser diffraction particle size analyzer (Malvern, Mastersizer 3000) and was taken as the median value of the particle size distribution.
[0020] In addition, the thermoelectric semiconductor particles are preferably heat-treated in advance (the "heat treatment" here is different from the "annealing treatment" performed in the annealing treatment step in the manufacturing method of the thermoelectric conversion material layer of the present invention described later). By performing the heat treatment, the crystallinity of the thermoelectric semiconductor particles is improved, and further, the surface oxide film of the thermoelectric semiconductor particles is removed, so that the Seebeck coefficient or Peltier coefficient of the thermoelectric conversion material is increased, and the thermoelectric figure of merit can be further improved. The heat treatment is not particularly limited, but is preferably performed in an inert gas atmosphere such as nitrogen or argon, a reducing gas atmosphere such as hydrogen, or under vacuum conditions with a controlled gas flow rate, before preparing the thermoelectric semiconductor composition, so as not to adversely affect the thermoelectric semiconductor particles, and more preferably in a mixed gas atmosphere of an inert gas and a reducing gas. The specific temperature conditions depend on the thermoelectric semiconductor particles used, but it is usually preferable to perform the heat treatment at a temperature below the melting point of the particles and at 100 to 1500°C for several minutes to several tens of hours.
[0021] (Heat-resistant resin) In the thermoelectric semiconductor composition used in the present invention, a heat-resistant resin is preferably used from the viewpoint of annealing the thermoelectric semiconductor material at a high temperature. The resin acts as a binder between the thermoelectric semiconductor material (thermoelectric semiconductor particles), and can increase the flexibility of the thermoelectric conversion module, and also makes it easier to form a thin film by coating or the like. The heat-resistant resin is not particularly limited, but is preferably a heat-resistant resin that maintains various physical properties such as mechanical strength and thermal conductivity as a resin without being impaired when the thin film made of the thermoelectric semiconductor composition is subjected to annealing or the like to cause crystal growth of the thermoelectric semiconductor particles. The heat-resistant resin is preferably a polyamide resin, a polyamideimide resin, a polyimide resin, or an epoxy resin, because it has higher heat resistance and does not adversely affect the crystal growth of the thermoelectric semiconductor particles in the thin film, and more preferably a polyamide resin, a polyamideimide resin, or a polyimide resin, because it has excellent flexibility. In the present invention, the term "polyimide resin" collectively refers to polyimides and their precursors.
[0022] The heat-resistant resin preferably has a decomposition temperature of 300° C. or higher. If the decomposition temperature is within the above range, the resin can maintain its flexibility without losing its function as a binder, even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0023] The heat-resistant resin preferably has a mass loss rate of 10% or less, more preferably 5% or less, and even more preferably 1% or less, at 300° C. as measured by thermogravimetry (TG). If the mass loss rate is within the above range, the resin does not lose its function as a binder and can maintain the flexibility of the thermoelectric conversion material layer, even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0024] The amount of the heat-resistant resin in the thermoelectric semiconductor composition is 0.1 to 40% by mass, preferably 0.5 to 20% by mass, more preferably 1 to 20% by mass, and further preferably 2 to 15% by mass. When the amount of the heat-resistant resin is within the above range, the resin functions as a binder for the thermoelectric semiconductor material, making it easier to form a thin film, and a film having both high thermoelectric performance and film strength can be obtained.
[0025] (Ionic Liquid) The ionic liquid used in the present invention is a molten salt formed by combining a cation and an anion, and refers to a salt that can exist in a liquid state in any temperature range of -50 to 400 ° C. In other words, the ionic liquid is an ionic compound having a melting point in the range of -50 ° C. to less than 400 ° C. The melting point of the ionic liquid is preferably -25 ° C. to 200 ° C., more preferably 0 ° C. to 150 ° C. Ionic liquids have characteristics such as extremely low vapor pressure and non-volatility, excellent thermal stability and electrochemical stability, low viscosity, and high ionic conductivity, and therefore can effectively suppress the reduction of electrical conductivity between thermoelectric semiconductor particles as a conductive auxiliary. In addition, ionic liquids exhibit high polarity based on an aprotic ionic structure and have excellent compatibility with heat-resistant resins, so that the electrical conductivity of the thermoelectric conversion material layer can be made uniform.
[0026] The ionic liquid may be a known or commercially available one. For example, a mixture of a cationic component such as a pyridinium, pyrimidinium, pyrazolium, pyrrolidinium, piperidinium, imidazolium, etc., a nitrogen-containing cyclic cationic compound and a derivative thereof; an amine-based cation of tetraalkylammonium and a derivative thereof; a phosphine-based cation such as phosphonium, trialkylsulfonium, tetraalkylphosphonium, etc. and a derivative thereof; a lithium cation and a derivative thereof; and a mixture of a Cl - , AlCl4 - , Al2Cl7 - , ClO4 - Chloride ions such as Br - bromide ions, such as I - Iodide ions such as BF4 -, PF6 - Fluoride ions such as F(HF) n - Halide anions such as NO3 - , CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (FSO2)2N - , (CF3SO2)2N - , (CF3SO2)3C - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , F(HF)n - , (CN)2N - , C4F9SO3 - , (C2F5SO2)2N - , C3F7COO - , (CF3SO2)(CF3CO)N - and an anion component such as the above.
[0027] Among the above ionic liquids, from the viewpoints of high temperature stability, compatibility with thermoelectric semiconductor particles and resins, and suppression of a decrease in the electrical conductivity of the gaps between thermoelectric semiconductor particles, it is preferable that the cationic component of the ionic liquid contains at least one selected from pyridinium cations and derivatives thereof, and imidazolium cations and derivatives thereof. It is preferable that the anionic component of the ionic liquid contains a halide anion, and Cl - , Br - and I - It is more preferable that the composition contains at least one selected from the following:
[0028] Specific examples of ionic liquids in which the cationic component contains a pyridinium cation and a derivative thereof include 4-methyl-butylpyridinium chloride, 3-methyl-butylpyridinium chloride, 4-methyl-hexylpyridinium chloride, 3-methyl-hexylpyridinium chloride, 4-methyl-octylpyridinium chloride, 3-methyl-octylpyridinium chloride, 3,4-dimethyl-butylpyridinium chloride, 3,5-dimethyl-butylpyridinium chloride, 4-methyl-butylpyridinium tetrafluoroborate, 4-methyl-butylpyridinium hexafluorophosphate, 1-butylpyridinium bromide, 1-butyl-4-methylpyridinium bromide, 1-butyl-4-methylpyridinium hexafluorophosphate, and 1-butyl-4-methylpyridinium iodide. Of these, 1-butylpyridinium bromide, 1-butyl-4-methylpyridinium bromide, 1-butyl-4-methylpyridinium hexafluorophosphate, and 1-butyl-4-methylpyridinium iodide are preferred.
[0029] Specific examples of ionic liquids in which the cationic component contains an imidazolium cation and a derivative thereof include [1-butyl-3-(2-hydroxyethyl)imidazolium bromide], [1-butyl-3-(2-hydroxyethyl)imidazolium tetrafluoroborate], 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, 1-octyl-3-methylimidazolium chloride, 1-decyl-3-methylimidazolium chloride, and 1-decyl-3-methylimidazolium chloride. Examples of the imidazolium bromide include 1-dodecyl-3-methylimidazolium chloride, 1-tetradecyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-hexyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-methyl-3-butylimidazolium methyl sulfate, and 1,3-dibutylimidazolium methyl sulfate. Among these, [1-butyl-3-(2-hydroxyethyl)imidazolium bromide] and [1-butyl-3-(2-hydroxyethyl)imidazolium tetrafluoroborate] are preferred.
[0030] The above ionic liquid has an electrical conductivity of 10 -7 S / cm or more is preferable, and 10 -6 If the electrical conductivity is in the above range, the conductive additive can effectively suppress the decrease in electrical conductivity between thermoelectric semiconductor particles.
[0031] The ionic liquid preferably has a decomposition temperature of 300° C. or higher. If the decomposition temperature is within the above range, the effect as a conductive auxiliary agent can be maintained even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0032] Furthermore, the ionic liquid preferably has a mass loss rate of 10% or less, more preferably 5% or less, and even more preferably 1% or less at 300° C. as measured by thermogravimetry (TG). If the mass loss rate is within the above range, the ionic liquid can maintain its effect as a conductive auxiliary even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0033] The amount of the ionic liquid in the thermoelectric semiconductor composition is preferably 0.01 to 50% by mass, more preferably 0.5 to 30% by mass, and further preferably 1.0 to 20% by mass. When the amount of the ionic liquid is within the above range, a decrease in electrical conductivity is effectively suppressed, and a film having high thermoelectric performance is obtained.
[0034] (Inorganic ionic compounds) The inorganic ionic compound used in the present invention is a compound composed of at least a cation and an anion. The inorganic ionic compound is a solid at room temperature, has a melting point at any temperature in the temperature range of 400 to 900°C, and has characteristics such as high ionic conductivity, so that it can suppress the decrease in electrical conductivity between thermoelectric semiconductor particles as a conductive auxiliary.
[0035] As the cation, a metal cation is used. Examples of the metal cation include alkali metal cations, alkaline earth metal cations, typical metal cations and transition metal cations, with alkali metal cations and alkaline earth metal cations being more preferred. Examples of alkali metal cations include Li + , Na + , K + , Rb + , Cs + and Fr + etc. Examples of alkaline earth metal cations include Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ etc.
[0036] The anion may be, for example, F - , Cl - , Br - , I - , O.H. - , C.N. - , NO3 - , NO2 - , ClO - , ClO2 - , ClO3 - , ClO4 - , CrO4 2- , HSO4 - , SCN - , BF4 - , PF6 - etc.
[0037] The inorganic ionic compound may be any known or commercially available inorganic ionic compound. For example, a cationic component such as potassium cation, sodium cation, or lithium cation and a Cl - , AlCl4 - , Al2Cl7 - , ClO4 - Chloride ions such as Br - bromide ions, such as I - Iodide ions such as BF4 - , PF6 - Fluoride ions such as F(HF) n - Halide anions such as NO3 - , O.H. - , C.N. - and an anion component such as the above.
[0038] Among the above inorganic ionic compounds, from the viewpoints of high temperature stability, compatibility with thermoelectric semiconductor particles and resin, and suppression of a decrease in the electrical conductivity of the gaps between thermoelectric semiconductor particles, it is preferable that the cationic component of the inorganic ionic compound contains at least one selected from potassium, sodium, and lithium. In addition, it is preferable that the anionic component of the inorganic ionic compound contains a halide anion, and Cl is preferably 0.01 to 0.01. - , Br - , and I -It is more preferable that the composition contains at least one selected from the following:
[0039] Specific examples of inorganic ionic compounds in which the cationic component contains a potassium cation include KBr, KI, KCl, KF, KOH, K2CO3, etc. Among these, KBr and KI are preferred. Specific examples of inorganic ionic compounds in which the cationic component contains a sodium cation include NaBr, NaI, NaOH, NaF, Na2CO3, etc. Among these, NaBr and NaI are preferred. Specific examples of inorganic ionic compounds in which the cationic component contains a lithium cation include LiF, LiOH, LiNO3, etc. Among these, LiF and LiOH are preferred.
[0040] The above inorganic ionic compounds have an electrical conductivity of 10 -7 S / cm or more is preferable, and 10 -6 If the electrical conductivity is in the above range, the conductive additive can effectively suppress the decrease in electrical conductivity between thermoelectric semiconductor particles.
[0041] The inorganic ionic compound preferably has a decomposition temperature of 400° C. or higher. If the decomposition temperature is within the above range, the effect as a conductive auxiliary agent can be maintained even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0042] Furthermore, the inorganic ionic compound preferably has a mass loss rate of 10% or less, more preferably 5% or less, and even more preferably 1% or less at 400° C. as measured by thermogravimetry (TG). If the mass loss rate is within the above range, the compound can maintain its effect as a conductive auxiliary even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0043] The amount of the inorganic ionic compound in the thermoelectric semiconductor composition is preferably 0.01 to 50 mass%, more preferably 0.5 to 30 mass%, and further preferably 1.0 to 10 mass%. When the amount of the inorganic ionic compound is within the above range, the decrease in electrical conductivity can be effectively suppressed, and as a result, a film with improved thermoelectric performance can be obtained. In addition, when an inorganic ionic compound and an ionic liquid are used in combination, the total content of the inorganic ionic compound and the ionic liquid in the thermoelectric semiconductor composition is preferably 0.01 to 50 mass%, more preferably 0.5 to 30 mass%, and even more preferably 1.0 to 10 mass%.
[0044] (Other additives) In addition to the components other than those described above, the thermoelectric semiconductor composition used in the present invention may further contain, as necessary, other additives such as dispersants, film-forming assistants, light stabilizers, antioxidants, tackifiers, plasticizers, colorants, resin stabilizers, fillers, pigments, conductive fillers, conductive polymers, curing agents, etc. These additives may be used alone or in combination of two or more.
[0045] The thermoelectric conversion material layer of the present invention has improved electrical conductivity, and by using it as a thermoelectric conversion material layer of a thermoelectric conversion module, a thermoelectric conversion module with high thermoelectric performance can be obtained.
[0046] [Method of manufacturing thermoelectric conversion material layer] The method for producing a thermoelectric conversion material layer of the present invention is a method for producing a thermoelectric conversion material layer consisting of a coating film of a thermoelectric semiconductor composition, and is characterized by comprising the steps of: (A) forming a thermoelectric conversion material layer; (B) drying the thermoelectric conversion material layer obtained in the step (A); (C) pressurizing the thermoelectric conversion material layer after drying obtained in the step (B); and (D) annealing the pressurized thermoelectric conversion material layer obtained in the step (C). In the method for manufacturing a thermoelectric conversion material layer of the present invention, after forming a thermoelectric conversion material layer, it is dried at a predetermined temperature, and then the upper surface of the thermoelectric conversion material layer is pressed at a predetermined pressure to reduce the volume of voids in the thermoelectric conversion material layer, and then an annealing treatment is performed, thereby obtaining a thermoelectric conversion material layer with improved electrical conductivity.
[0047] FIG. 3 is an explanatory diagram showing an example of a method for producing a thermoelectric conversion material layer according to the present invention in the order of steps, in which (a) is a cross-sectional view showing an embodiment in which a thermoelectric conversion material layer 2s is formed on a substrate 1a, in which the thermoelectric conversion material layer 2s is formed as a coating film (including voids 3a) on the substrate 1a and dried at a predetermined temperature; 1(b) is a cross-sectional view showing an aspect after a press pressure part 5 is placed opposite an upper surface of a thermoelectric conversion material layer 2s, in which the thermoelectric conversion material layer 2s after drying obtained in (a) is cooled to room temperature, and then the thermoelectric conversion material layer 2s and the press pressure part 5 are placed opposite each other; 1C is a cross-sectional view showing a state after the press part 5 has been pressed against the upper surface of the thermoelectric conversion material layer 2s and then the press part 5 has been released from the thermoelectric conversion material layer 2s. Thereafter, an annealing treatment is performed to obtain the thermoelectric conversion material layer 2t of the present invention (including the void portions 4a in which the number and volume of the voids are reduced).
[0048] In a preferred embodiment, the thermoelectric conversion material layer may be formed as a solid film on a substrate and then diced into chips of the desired size. In another preferred embodiment, a coating film of the size of the thermoelectric conversion material chips may be formed on the substrate. Furthermore, in terms of shape controllability of the thermoelectric conversion material layer, in a more preferred embodiment, the thermoelectric conversion material layer may be formed using a lattice-shaped pattern frame member including spaced apart openings having the shape of the thermoelectric conversion material chips. The chip size is, for example, about 0.1 to 20 mm on the short side and about 0.2 to 25 mm on the long side.
[0049] A method for producing a thermoelectric conversion material layer when using a lattice-shaped pattern frame member including spaced apart openings each having the shape of a chip of the thermoelectric conversion material is, for example, as follows. (p) placing a grid-like patterned frame member including spaced apart openings having the shape of chips of a thermoelectric conversion material on the substrate; (q) forming a coating film of a thermoelectric conversion material layer on the opening of the pattern frame member, and drying it at a predetermined temperature; (r) After cooling the dried thermoelectric conversion material layer obtained in (q) to room temperature, the thermoelectric conversion material layer is faced to a press pressure unit (corresponding to press pressure unit 5 in FIG. 3 ); (t) applying pressure to the upper surface of the thermoelectric conversion material layer with a press pressure unit to reduce the number and volume of voids in the thermoelectric conversion material layer, releasing the press pressure unit from the thermoelectric conversion material layer, and further releasing the pattern frame member; (u) Thereafter, the thermoelectric conversion material layer, which reflects the shape of the openings of the pattern frame member obtained on the substrate, is subjected to an annealing treatment, thereby obtaining a chip-shaped thermoelectric conversion material layer of the present invention. The opening is not particularly limited, but may have a shape that is reflected in the shape of the chip of thermoelectric conversion material after the pattern frame member is released, and is preferably rectangular, square, or circular, and more preferably rectangular or square. From the viewpoint of ease of formation, stainless steel, copper, etc. can be used as the pattern frame member.
[0050] (A) Thermoelectric conversion material layer formation process The thermoelectric conversion material layer formation process is a process of forming a thermoelectric conversion material layer on a substrate. For example, in FIG. 3(a), it is a process of applying a thermoelectric semiconductor composition onto a substrate 1a to form a thermoelectric conversion material layer 2s.
[0051] (substrate) The substrate is not particularly limited, and examples thereof include glass, silicon, ceramic, metal, plastic, etc. From the viewpoint of performing the annealing treatment at a high temperature, glass, silicon, ceramic, and metal are preferred, and from the viewpoint of dimensional stability after the heat treatment, glass, silicon, and ceramic are more preferred. From the viewpoints of process and dimensional stability, the thickness of the substrate may be 100 to 10,000 μm.
[0052] (Thermoelectric semiconductor composition) The thermoelectric semiconductor composition used in the present invention may be the same as that described above. The preferred materials and blending amounts of the thermoelectric semiconductor material, heat-resistant resin, ionic liquid, inorganic ionic compound, etc. are also the same.
[0053] (Method for preparing thermoelectric semiconductor composition) The method for preparing the thermoelectric semiconductor composition used in the present invention is not particularly limited, and the thermoelectric semiconductor composition may be prepared by mixing and dispersing the thermoelectric semiconductor particles, the heat-resistant resin, one or both of the ionic liquid and the inorganic ionic compound, and if necessary, the other additives and a solvent, using a known method such as an ultrasonic homogenizer, a spiral mixer, a planetary mixer, a disperser, or a hybrid mixer. Examples of the solvent include toluene, ethyl acetate, methyl ethyl ketone, alcohol, tetrahydrofuran, methylpyrrolidone, ethyl cellosolve, and the like. These solvents may be used alone or in combination of two or more. The solid content concentration of the thermoelectric semiconductor composition is not particularly limited as long as the composition has a viscosity suitable for coating.
[0054] The thin film made of the thermoelectric semiconductor composition can be formed, for example, by applying the thermoelectric semiconductor composition onto the substrate and drying it.
[0055] Methods for applying the thermoelectric semiconductor composition onto a substrate include, but are not limited to, known methods such as screen printing, flexographic printing, gravure printing, spin coating, dip coating, die coating, spray coating, bar coating, doctor blade, applicator, etc. When forming a coating film in a pattern, screen printing, stencil printing, slot die coating, etc., which can easily form a pattern using a screen plate having a desired pattern, are preferably used.
[0056] (B) Thermoelectric conversion material layer drying process The thermoelectric conversion material layer drying step is a step of drying the thermoelectric conversion material layer obtained in step (A), and in FIG. 3(a), for example, is a step of drying the thermoelectric conversion material layer 2s on the substrate 1a. The drying method may be a conventionally known method such as hot air drying, heat roll drying, infrared irradiation, etc. The heating temperature is usually 80 to 170°C, preferably 100 to 150°C, more preferably 110 to 145°C, and further preferably 120 to 140°C. The heating time varies depending on the heating method, but is usually 30 seconds to 5 hours, preferably 1 minute to 3 hours, more preferably 5 minutes to 2 hours, and further preferably 10 minutes to 50 minutes. If the heating temperature and heating time are within these ranges, this tends to lead to an improvement in the electrical conductivity of the thermoelectric conversion material layer after pressure application and annealing treatment. Furthermore, when a solvent is used in the preparation of the thermoelectric semiconductor composition, the heating temperature may be within a temperature range in which the solvent used can be dried, or may be a temperature range lower than this.
[0057] (C) Thermoelectric conversion material layer pressure process The thermoelectric conversion material layer pressurizing step is a step of pressurizing the thermoelectric conversion material layer after drying obtained in step (B). For example, in FIG. 3(b), it is a step of pressing the upper surface of the thermoelectric conversion material layer 2s with a press pressure section 5.
[0058] In one embodiment, the pressurization is preferably performed under atmospheric pressure after cooling the thermoelectric conversion material layer after drying obtained in step (B) to room temperature, while in another embodiment, the pressurization is preferably performed while maintaining the drying temperature without cooling the thermoelectric conversion material layer after drying obtained in step (B) to room temperature, and then the layer is subjected to the annealing treatment step described below as the next step. Examples of the pressurizing method include a method using a physical pressurizing means such as a hydraulic press, a vacuum press, or a weight. The amount of pressurization varies depending on the viscosity of the thermoelectric conversion material layer, the amount of voids, etc., but is usually 0.1 to 80 MPa, preferably 1.0 to 60 MPa, more preferably 5 to 50 MPa, and even more preferably 10 to 42 MPa. The pressurization may be increased to a predetermined amount at once, but is appropriately adjusted from the viewpoint of maintaining the shape stability of the thermoelectric conversion material layer and reducing the voids in the thermoelectric conversion material layer as much as possible to improve the filling rate of the thermoelectric conversion material. The amount of pressurization is usually increased to a predetermined amount at 0.1 to 50 MPa / min, preferably 0.5 to 30 MPa / min, and even more preferably 1.0 to 10 MPa / min. The pressurizing time varies depending on the pressurizing method, but is usually 5 seconds to 5 hours, preferably 30 seconds to 3 hours, more preferably 5 minutes to 2 hours, and further preferably 10 minutes to 1 hour. If the pressure amount and pressure time are within this range, the packing rate increases, and the electrical conductivity of the thermoelectric conversion material layer after annealing treatment tends to improve.
[0059] (D) Annealing process The annealing process is a process of annealing the pressurized thermoelectric conversion material layer obtained in the process (C) above. For example, in FIG. 3(c), it is a process of annealing the pressurized thermoelectric conversion material layer 2s at an annealing temperature (after the annealing process, a thermoelectric conversion material layer 2t is obtained). The thermoelectric conversion material layer is formed as a thin film, dried, and then annealed to stabilize the thermoelectric performance and induce crystal growth of the thermoelectric semiconductor particles in the thin film, thereby further improving the thermoelectric performance.
[0060] The annealing treatment is carried out with or without applying pressure to the thermoelectric conversion material layer. When applying pressure, the pressure is usually 0.1 to 80 MPa, preferably 1.0 to 60 MPa, more preferably 5 to 50 MPa, and further preferably 10 to 42 MPa. Furthermore, although not particularly limited, the annealing treatment is usually performed under an inert gas atmosphere such as nitrogen or argon, under a reducing gas atmosphere, or under vacuum conditions with the gas flow rate controlled, and although it depends on the thermoelectric semiconductor material, heat-resistant resin, ionic liquid, inorganic ionic compound, etc. used in the thermoelectric semiconductor composition, the annealing temperature is usually 100 to 600°C for several minutes to several tens of hours, preferably 250 to 450°C for several minutes to several tens of hours.
[0061] The thickness of the thermoelectric conversion material layer is not particularly limited as long as the shape stability and thermoelectric performance are not impaired by pressure, as described above.
[0062] According to the method for producing a thermoelectric conversion material layer of the present invention, a thermoelectric conversion material layer having improved electrical conductivity can be produced by a simple method. EXAMPLES
[0063] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.
[0064] The filling rate of the thermoelectric semiconductor composition in the thermoelectric conversion material layers produced in the Examples and Comparative Examples and the electrical conductivity were evaluated by the following methods. (a) Evaluation of filling rate For the thermoelectric conversion material layers produced in the examples and comparative examples, a longitudinal section including the center of the thermoelectric conversion material layer was prepared using a polishing device (manufactured by Refine Tech Co., Ltd., model name: Refine Polisher HV), and the longitudinal section was observed using FE-SEM / EDX (FE-SEM: manufactured by Hitachi High-Technologies Corporation, model name: S-4700). Next, the filling rate, which is defined as the ratio of the area of the thermoelectric semiconductor composition to the area of the longitudinal section of the thermoelectric conversion material layer, was calculated using Image J (image processing software, ver. 1.44P). In measuring the filling rate, a 500x magnification SEM image (longitudinal cross section) was used, and the measurement range was set to a range surrounded by 1280 pixels in the width direction and 220 pixels in the thickness direction based on the boundary between the thermoelectric conversion material layer and the alumina substrate, and the image was cut out. The cut-out image was binarized by setting the contrast to the maximum value in "Brightness / Contrast", and the dark areas in the binarization process were considered to be voids and the bright areas were considered to be the thermoelectric semiconductor composition, and the filling rate of the thermoelectric semiconductor composition was calculated using "Threshold". The filling rate was calculated for three SEM images and the average value was calculated. The image to be cut out is selected within the region of the longitudinal section. For example, in (a) of Figure 2, a region that does not exceed X in the width direction of the longitudinal section and Dmin in the thickness direction was selected so as to avoid incorporating voids (air layers) around the thermoelectric conversion material layer. (b) Evaluation of electrical conductivity For the thermoelectric conversion material layers produced in the examples and comparative examples, the surface resistance was measured by the four-terminal method using a low resistance measurement device (manufactured by HIOKI Corporation, model number: RM3545) in an environment of 25°C and 60% RH, and the electrical conductivity was calculated.
[0065] Example 1 <Preparation of thermoelectric conversion material layer> (1) Preparation of thermoelectric semiconductor composition (Preparation of thermoelectric semiconductor particles) P-type bismuth telluride Bi, a bismuth-tellurium based thermoelectric semiconductor material 0.4 Te3Sb 1.6 (manufactured by Kojundo Chemical Laboratory, particle size: 180 μm) was pulverized in a nitrogen gas atmosphere using a planetary ball mill (manufactured by Fritsch Japan, Premium line P-7) to produce thermoelectric semiconductor particles with an average particle size of 2.0 μm. The particle size distribution of the thermoelectric semiconductor particles obtained by pulverization was measured using a laser diffraction particle size analyzer (manufactured by Malvern, Mastersizer 3000). (Preparation of Coating Solution of Thermoelectric Semiconductor Composition) The p-type bismuth telluride Bi obtained above 0.4 Te3Sb 1.6A coating liquid was prepared comprising a thermoelectric semiconductor composition in which 82.5% by mass of particles, 3.2% by mass (solid content) of polyamic acid (Ube Industries, Ltd., U-Varnish A, solvent: N-methylpyrrolidone, solid content concentration: 18% by mass) which is a polyimide precursor as a heat-resistant resin, and 14.3% by mass of 1-butylpyridinium bromide as an ionic liquid were mixed and dispersed. (2) Formation of thermoelectric conversion material layer and pressure treatment The coating liquid prepared in (1) above was printed as a solid film on an alumina substrate (manufactured by Kyocera Corporation, product name: Alumina substrate A0476T, 100 mm × 100 mm, thickness: 1 mm) using an applicator, and dried at a temperature of 140°C for 40 minutes in an argon atmosphere to form a thin film (thermoelectric conversion material layer before annealing treatment) with a thickness of 37 μm. Next, the dried thermoelectric conversion material layer was cooled to room temperature, and the alumina substrate on which the thermoelectric conversion material layer was printed was cut into a size of 5 mm × 15 mm. After that, a hydraulic press (manufactured by Tester Sangyo Co., Ltd., model name: SA-30 benchtop test press) was used to uniformly apply pressure to the entire upper surface of the thermoelectric conversion material layer at 40.0 MPa for 1 minute at room temperature in the air. Furthermore, the thermoelectric conversion material layer obtained by the pressure treatment was heated at a heating rate of 5K / min in an atmosphere of a mixed gas of hydrogen and argon (hydrogen:argon = 3 volume %:97 volume %) and held at 430°C for 30 minutes to anneal the thermoelectric conversion material layer, causing crystal growth of the particles of the thermoelectric semiconductor material, and producing a thermoelectric conversion material layer. The resulting thermoelectric conversion material layer was evaluated for filling rate and electrical conductivity. The results are shown in Table 1.
[0066] Example 2 A thermoelectric conversion material layer was produced in the same manner as in Example 1, except that a pressure treatment of 30.0 MPa was uniformly performed on the entire upper surface of the thermoelectric conversion material layer. The resulting thermoelectric conversion material layer was evaluated for filling rate and electrical conductivity. The results are shown in Table 1.
[0067] Comparative Example 1 A thermoelectric conversion material layer was produced in the same manner as in Example 1, except that the pressure treatment was not performed, and the resulting thermoelectric conversion material layer was evaluated for filling rate and electrical conductivity. The results are shown in Table 1.
[0068] [Table 1]
[0069] It can be seen that in Examples 1 and 2, in which the filling rate of the thermoelectric conversion material in the thermoelectric conversion material layer made of a coating film of a thermoelectric semiconductor composition satisfies the requirement of the present invention, the electrical conductivity is increased by 50 to 118% compared to Comparative Example 1, in which the filling rate is outside the range of the requirement of the present invention. Therefore, by applying the thermoelectric conversion material layer and the method for producing the same of the present invention to a thermoelectric conversion module, it is possible to improve the thermoelectric performance of the thermoelectric conversion module. [Industrial Applicability]
[0070] According to the thermoelectric conversion material layer made of a coating film of the thermoelectric semiconductor composition of the present invention and the manufacturing method thereof, the electrical conductivity of the thermoelectric conversion material layer is increased, so that by incorporating the thermoelectric conversion material layer of the present invention into a thermoelectric conversion module, it is expected that the thermoelectric performance will be improved. At the same time, the obtained thermoelectric conversion module has flexibility and the possibility of realizing a thinner (smaller, lighter) module compared to a thermoelectric conversion module using a conventional sintered body of a thermoelectric semiconductor material. A thermoelectric conversion module using the above-mentioned thermoelectric conversion material layer can be used for power generation purposes, such as converting exhaust heat from various combustion furnaces, such as factories, waste combustion furnaces, and cement combustion furnaces, exhaust heat from automobile combustion gases, and exhaust heat from electronic devices into electricity. As cooling purposes, the module can be used in the field of electronic equipment, for example, to control the temperature of various sensors, such as semiconductor elements, such as CCDs (Charge Coupled Devices), MEMS (Micro Electro Mechanical Systems), and light-receiving elements. [Explanation of symbols]
[0071] 1a: Substrate 1b: Alumina substrate 2, 2s, 2t: Thermoelectric conversion material layer 3:Void part 3a,4a:Void part 3b: Void (Comparative Example 1) 4b: Void portion (Example 1) 5: Press pressure section X: Length (width) Y: Length (depth direction) D: Thickness (thickness direction) Dmax: Maximum thickness in the thickness direction (longitudinal section) Dmin: Minimum thickness in the thickness direction (vertical section) C: Center of the thermoelectric conversion material layer
Claims
1. A thermoelectric conversion material layer formed of a coating film of a thermoelectric semiconductor composition, The thermoelectric semiconductor composition includes a thermoelectric semiconductor material and a heat-resistant resin, the thermoelectric conversion material layer has voids, The thickness of the thermoelectric conversion material layer is 3 to 600 μm, the heat-resistant resin is a polyimide resin, a polyamide resin, or a polyamideimide resin; a filling rate defined as a ratio of an area of the thermoelectric semiconductor composition to an area of a longitudinal cross section including a central portion of the thermoelectric conversion material layer, the filling rate being 0.800 or more and less than 1.
000.
2. 2. The thermoelectric conversion material layer according to claim 1, wherein the thermoelectric semiconductor material is a bismuth-tellurium based thermoelectric semiconductor material, a telluride based thermoelectric semiconductor material, an antimony-tellurium based thermoelectric semiconductor material, or a bismuth selenide based thermoelectric semiconductor material.
3. The thermoelectric conversion material layer according to claim 1 or 2, wherein the thermoelectric semiconductor composition further contains an ionic liquid and / or an inorganic ionic compound.
4. The thermoelectric conversion material layer according to any one of claims 1 to 3, wherein the filling rate is 0.850 to 0.
999.
5. A thermoelectric conversion material layer comprising a coating film of a thermoelectric semiconductor composition, The thermoelectric semiconductor composition includes a thermoelectric semiconductor material and a heat-resistant resin, the thermoelectric conversion material layer has voids, The thickness of the thermoelectric conversion material layer is 3 to 600 μm, When the ratio of the area of the thermoelectric semiconductor composition to the area of a vertical cross section including a central portion of the thermoelectric conversion material layer is defined as a filling rate, the filling rate is 0.800 or more and less than 1.
000. A method for producing a thermoelectric conversion material layer, comprising: (A) forming a thermoelectric conversion material layer; (B) a step of drying the thermoelectric conversion material layer obtained in the step (A); (C) a step of pressing the thermoelectric conversion material layer after drying obtained in the step (B); and (D) a step of annealing the pressed thermoelectric conversion material layer obtained in the step (C); Including, The pressurization is performed at 5 to 60 MPa. A method for producing a thermoelectric conversion material layer.
6. The method for producing a thermoelectric conversion material layer according to claim 5, wherein the annealing temperature is 250 to 600°C.
Citation Information
Patent Citations
Thermoelectric conversion material and its manufacturing method
JP1999097751A
Thermoelectric conversion material
JP2000012915A
Oxide thermoelectric conversion material
JP2002084006A
Thermoelectric conversion element and manufacturing method of it
JP2002223013A
Thermoelectric device
JP2003258323A